Topological Photonics: Gauge‐Induced Floquet Topological States in Photonic Waveguides (Laser Photonics Rev. 15(8)/2021). Issue 8 (13th August 2021) - Song, Wange; Chen, Yuxin; Li, Hanmeng; Gao, Shenglun; Wu, Shengjie; Chen, Chen; Zhu, Shining; Li, Tao
Abstract : In article number 2000584, Tao Li and co‐workers from Nanjing University experimentally demonstrated topological π modes induced by Floquet gauge transition in a silicon waveguides platform. The flexible control of the Floquet gauge provides new degrees of freedom to manipulate the topological modes and enables interesting functionalities such as asymmetric topological transport, i.e., the localization is protected only for light propagating in one direction.